The Role Of Magic Oil As A Modification Substitute Of Plant-Based Side Dish Tofu Curry Based On Nutritional Content And Organoleptic Properties At Dr. Moewardi Regional General Hospital - Martini; Fadzillah; Hidayah, Halimah Nurul (Indonesian Basic and Experimental Health Sciences, 2024)
Background: The use of spices and herbs in the nutrition installation of Dr. Moewardi Regional General Hospital to make kitchen seasoning generates waste. The results of the researcher's interview with officers at the Food Production of Nutrition Installation of Dr. Moewardi Hospital, it was discovered that there was no utilization of spices and herbs waste. The spices and herbs waste was thrown away. Therefore, the researchers initiated to use herbs waste such as onion peels, garlic peels, leek, kaffir lime leaves, lemongrass, pandan leaves, and ginger as an alternative to additional seasoning in the form of oil called magic oil to increase the taste of patients' food, especially plant-based side dishes because based on the results of a study by Martini et al, 2022 it is discovered that there is more than 20% of leftover plant-based side dishes. Hence, a study to be conducted on the nutritional content and organoleptic properties of the variety of plant-based side dishes with the substitution of spice waste oil called magic oil. The plant-based side dish to be used was tofu curry because tofu curry was one of the plant-based side dishes used in previous study. In addition, tofu curry uses one of the basic seasonings, namely yellow seasoning. Purpose of the Study: Discovering the nutritional content and organoleptic properties of plant-based side dish modification with magic oil substitution. Method of the Study: The study used observational analytic design with its experimental nature. This study describes the nutritional content and organoleptic test of the modification of tofu curry with magic oil substitution. Nutritional content data were processed using  the Shapiro-Wilk test because the number of samples <50. The results were normally distributed, subsequently it was continued using the Anova test and Post-Hoc test. Data on organoleptic properties were processed using  the Shapiro-Wilk test  because the number of samples <50 results were not normally distributed, therefore it was tested using the Kruskal-Wallis test and continued with the Mann-Whitney test, providing that it was significant. Results: Based on the results of the Anova test, there was a significant difference in nutritional content data and continued with post-hoc  test. It was discovered that the treatment groups, namely B, C, and D, had high nutritional content compared to group A. The highest water, mineral, and protein content was discovered in group D, the highest fat and fiber content was discovered in group B,  and the highest carbohydrate content was discovered in group C. In organoleptic tests  consisting of color, taste, aroma, and texture, and it had a p value of <0.05 which means the data was not normally distributed therefore it used Kruskal-Wallis test  and continued with Mann-Whitney test,  providing that it was significant. After the Kruskal-Wallis test, the most influential was the taste factor in group D with a median value in taste of 3 which means “like”. Conclusion: The results of the Nutritional Content Test and Oraganoleptic Test of Tofu Curry Magic Oil Substitution show significant differences between group A (standard) and treatment groups, namely groups B, C and D. The higher the level of Magic Oil substitution, the higher the nutritional content and acceptability  of organoleptic  properties to the modification of Tofu Curry.